The ways to reduce the emigration of higher education professionals in the republic of Uzbekistan - Hamid Khudaybergenovich Abduramanov (Research Parks Publishers, 2020)
The article identifies the causes of emigration of specialists with higher education, the impact on economic security, scientific proposals and recommendations to reduce the emigration of specialists with higher education in the Republic of Uzbekistan.